How does 3D endovaginal ultrasound compare to magnetic resonance imaging in the evaluation of levator ani anatomy?. Issue 2 (15th December 2015) - Javadian, Pouya; O'Leary, Dena; Rostaminia, Ghazaleh; North, Justin; Wagner, Jason; Quiroz, Lieschen H.; Shobeiri, S. Abbas
Abstract : Introduction and Hypothesis: To compare magnetic resonance imaging (MRI) to 3D endovaginal ultrasound (EVUS) in the evaluation of major levator ani defects in women with pelvic floor disorders. Methods: A total of 21 subjects with pelvic floor with complaints of pelvic floor disorders were included in this study. EVUS imaging of the levator ani muscle (LAM) was performed in all subjects, and the LA muscle groups of interest evaluated were the puboanalis (PA), puborectalis (PR), and pubovisceralis (PV) muscles. The right and left subdivisions were evaluated separately, and classified as (i) normal, normal with only minor irregularities, grossly abnormal, or absent, or (ii) by the levator ani deficiency (LAD) score and classified by no defect (complete attachment of muscle to the pubic bone), <50% detachment or loss, >50% detachment or loss, and completely detached or complete muscle loss. Paired data were analyzed with McNemar's test or Bowker's test of symmetry. Results: When unilateral LAM subdivisions were classified as "normal, " "normal with minor irregularity, " "grossly abnormal, " and "absent, " there were no significant differences between MRI and EVUS by categorization of LAM defects. Comparing "normal" versus "abnormal, " there was no difference between imaging modalities. When compared by LAD score evaluation, there were no differences in the categorization of unilateral defects between MRI and EVUS. Conclusions: Endovaginal 3D US is comparable to MRI in its ability to identify both normal and abnormal LAM anatomy. Neurourol. Urodynam. 36:409–413, 2017 . © 2015 Wiley Periodicals, Inc.